Unequal childhoods : young children's lives in poor countries - Penn, Helen (London ; New York : Routledge, 2005)
While problems of childhood poverty are most widespread in developing countries, formidable inequalities exist in more prosperous countries. A major aim of the book is to address the question of unequal childhoodsand the ways in which they are.
Global inequalities -- Interpreting poverty -- Understanding early childhood -- Lending a helping hand -- Kazakhstan -- Swaziland -- India -- childhood and social inequality in Brazil -- The ethics of intervention.
Simultaneously published in the USA and Canada.
Includes bibliographical references (pages 195-208) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Children -- Developing countries -- Social conditions; Children -- Developing countries -- Case studies; Child development; Cross-cultural studies; International cooperation; Children; Developing Countries; Child Welfare; Child Development; Cross-Cultural Comparison; Early Intervention, Educational; International Cooperation; Socioeconomic Factors; Child; Enfants -- Développement.; Études transculturelles; Intervention précoce (Service social); Coopération internationale; Enfants; Enfance; children (people by age group); childhood; SOCIAL SCIENCE -- Children's Studies; International cooperation; Cross-cultural studies; Child development; Children; Children -- Social conditions; Developing countries; Kinderen; Armoede; Sociale ongelijkheid; Ontwikkelingslanden; Case studies